Interface region imaging spectrograph (IRIS) observations of the fractal dimension in the solar atmosphere - Aschwanden, Markus J.; Vilangot Nhalil, Nived (Frontiers in Astronomy and Space Sciences, 2022)
While previous work explored the fractality and self-organized criticality (SOC) of flares and nanoflares in wavelengths emitted in the solar corona (such as in hard X-rays, soft X-rays, and EUV wavelenghts), we focus here on impulsive phenomena in the photosphere and transition region, as observed with the Interface Region Imaging Spectrograph (IRIS) in the temperature range of T_e ≈ 10^4-10^6 K. We find the following fractal dimensions (in increasing order): D_A=1.21 ± 0.07 for photospheric granulation, D_A=1.29 ± 0.15 for plages in the transition region, D_A=1.54 ± 0.16 for sunspots in the transition region, D_A=1.59 ± 0.08 for magnetograms in active regions, D_A=1.56 ± 0.08 for EUV nanoflares, D_A=1.76 ± 0.14 for large solar flares, and up to D_A=1.89 ± 0.05 for the largest X-class flares. We interpret low values of the fractal dimension (1.0 D_A 1.5) in terms of sparse curvi-linear flow patterns, while high values of the fractal dimension (1.5 D_A 2.0) indicate near space-filling transport processes, such as chromospheric evaporation. Phenomena in the solar transition region appear to be consistent with SOC models, based on their size distributions of fractal areas A and (radiative) energies E, which show power law slopes of α_A^obs=2.51 ± 0.21 (with α_A^theo=2.33 predicted), and α_E^obs=2.03 ± 0.18 (with α_E^theo=1.80 predicted).